2017
DOI: 10.1111/jfd.12673
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of spaC‐type Erysipelothrix sp. isolates causing systemic disease in ornamental fish

Abstract: Since 2012, low-to-moderate mortality associated with an Erysipelothrix sp. bacterium has been reported in ornamental fish. Histological findings have included facial cellulitis, necrotizing dermatitis and myositis, and disseminated coelomitis with abundant intralesional Gram-positive bacterial colonies. Sixteen Erysipelothrix sp. isolates identified phenotypically as E. rhusiopathiae were recovered from diseased cyprinid and characid fish. Similar clinical and histological changes were also observed in zebraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 38 publications
1
41
0
4
Order By: Relevance
“…It was previously suggested that Spa proteins are likely important virulence factors associated with the pathogenic potential of E. rhusiopathiae in comparison to the less pathogenic E. tonsillarum (To and Nagai, 2007), and until recently, no Spa-related genes or proteins had been found in E. tonsillarum (To and Nagai, 2007;Shen et al, 2010). To our knowledge, the occurrence of spaA and spaB genes in E. tonsillarum has only been documented in one paper, among isolates from ornamental fish (Pomaranski et al, 2017). However, given that the species was defined based only on sequencing of the gyrB gene, it is conceivable that this isolate may have been misclassified.…”
Section: Spa Type and Correlation With Population Structure And Clinimentioning
confidence: 91%
See 1 more Smart Citation
“…It was previously suggested that Spa proteins are likely important virulence factors associated with the pathogenic potential of E. rhusiopathiae in comparison to the less pathogenic E. tonsillarum (To and Nagai, 2007), and until recently, no Spa-related genes or proteins had been found in E. tonsillarum (To and Nagai, 2007;Shen et al, 2010). To our knowledge, the occurrence of spaA and spaB genes in E. tonsillarum has only been documented in one paper, among isolates from ornamental fish (Pomaranski et al, 2017). However, given that the species was defined based only on sequencing of the gyrB gene, it is conceivable that this isolate may have been misclassified.…”
Section: Spa Type and Correlation With Population Structure And Clinimentioning
confidence: 91%
“…However, given that E. rhusiopathiae Clade 1 is more commonly isolated from marine mammals in captivity (Opriessnig et al, 2013;, and Erysipelothrix spp. carrying the spaC gene has recently been associated with disease in fish (Pomaranski et al, 2017), protecting against Erysipelothrix spp. carrying these Spa types could be of greater relevance for aquatic species.…”
Section: Spa Type and Correlation With Population Structure And Clinimentioning
confidence: 99%
“…In recent years Erysipelothrix spp. isolates containing SpaC have been associated with increased fish mortality (16) in the USA and very recently SpaC has also been identified in Erysipelothrix sp. 2 isolates from turkeys with increased mortality in Brazil (127).…”
Section: Protective Antigensmentioning
confidence: 99%
“…infection in pigs and is well-known by veterinarians and other occupations connected to the food animal industry (14). Today, erysipelas is also used to describe clinical manifestations associated with this bacterium in other species including mammals, fish, birds and reptiles (15,16). In humans, where the disease was first described in 1870 (17) since 1909 the term "erysipeloid" is used (18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation